2009
DOI: 10.1590/s0104-07072009000200007
|View full text |Cite
|
Sign up to set email alerts
|

O trabalho gerencial do enfermeiro na Rede Básica de Saúde

Abstract: RESUMO:Este estudo focaliza questões da gerência nos serviços públicos de saúde e têm como objetivo identificar elementos do trabalho gerencial do enfermeiro na Rede Básica de Saúde de Goiânia-GO. Pesquisa exploratória descritiva, de base quantitativa, realizada entre 2006/2007. Para a coleta de dados foi utilizada a entrevista estruturada com 44 enfermeiros gerentes de serviços. Foi construído um banco de dados, utilizando o Software Epi-Info versão 3.3.2. Os dados foram submetidos a um processo de codificaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
34

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 10 publications
0
18
0
34
Order By: Relevance
“…It is also an obstacle in analyzing the care provided, the conduct adopted, and the integration between vigilance, healthcare and information, as the professional becomes the normal source of care and not the record 13,18 . Although it is important to consider that the limited number of nurses available for the various programs of the Healthcare Services makes it harder to plan care, it is essential that they play a role in controlling TB, in terms of the care provided, overseeing the team focused on healthcare practice and vigilance measures, which includes carefully recording the care provided, and managing (individual and collective) care and healthcare services to enable coordination of the various elements involved [19][20][21][22] . This overview of the weaknesses of the nursing professionals is a complex process that starts with their training, which is focused on technical development, to the detriment of management skills 19 .…”
Section: Mendesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also an obstacle in analyzing the care provided, the conduct adopted, and the integration between vigilance, healthcare and information, as the professional becomes the normal source of care and not the record 13,18 . Although it is important to consider that the limited number of nurses available for the various programs of the Healthcare Services makes it harder to plan care, it is essential that they play a role in controlling TB, in terms of the care provided, overseeing the team focused on healthcare practice and vigilance measures, which includes carefully recording the care provided, and managing (individual and collective) care and healthcare services to enable coordination of the various elements involved [19][20][21][22] . This overview of the weaknesses of the nursing professionals is a complex process that starts with their training, which is focused on technical development, to the detriment of management skills 19 .…”
Section: Mendesmentioning
confidence: 99%
“…Although it is important to consider that the limited number of nurses available for the various programs of the Healthcare Services makes it harder to plan care, it is essential that they play a role in controlling TB, in terms of the care provided, overseeing the team focused on healthcare practice and vigilance measures, which includes carefully recording the care provided, and managing (individual and collective) care and healthcare services to enable coordination of the various elements involved [19][20][21][22] . This overview of the weaknesses of the nursing professionals is a complex process that starts with their training, which is focused on technical development, to the detriment of management skills 19 . Recording TB healthcare actions and vigilance, such as DOT and sputum tests during treatment could help monitor, plan and assess the care provided, especially for disease control 3,[23][24][25][26] .…”
Section: Mendesmentioning
confidence: 99%
“…As a manager or coordinator, the nurse increases the importance of his or her activities, in relation to the team, since he or she expands his or her own role beyond the core practice, adding more assignments, playing a key role in the development of work processes and attention to healthcare in a USF. A study performed (5) concluded that nurses who are coordinators of family healthcare units, use most of their time, during the workday, performing activities that are essentially managerial. Similar results were found in this study.…”
Section: Coordination Activitiesmentioning
confidence: 99%
“…The conducting of essentially administrative and bureaucratic activities by nurses has been a point of discussion, as they make up a whole other set of activities that go beyond healthcare practices. (3)(4)(5) Given these initial reflections and the objective of analyzing the challenges and the potential for coordination of the Family Healthcare Units, done by nurses, and based on the referential analyses of working in healthcare, (6) we ask the following research question: how should the nurse's coordination process in the Family Healthcare Units be configured?…”
Section: Introductionmentioning
confidence: 99%
“…São consideradas as intersecções entre saúde e educação, com a adequação do ensino para a produção de conhecimentos e serviços com base nas necessidades sociais. 5 Este estudo justifica-se pela importância do reconhecimento e caracterização das atividades proporcionadas para a formação do enfermeiro no contexto da atenção básica. A contribuição pretendida segue no sentido de sustentar discussões sobre acompanhamento e avaliação curricular que busquem relacionar a realidade da formação profissional do enfermeiro com as necessidades do sistema de saúde e as DCNs.…”
Section: Introductionunclassified